Non-monotonicity from constructing semantic representations - Fernando, Tim (Proceedings of the Amsterdam Colloquium, 1999)
A standard approach to non-monotonicity locates the phenomenon in preferences between models, against which certain well-formed formulas or semantic representations (SRs) are interpreted. Such an approach assumes a construction of suitable SRs for natural language discourse - arguably the main challenge in formal linguistics (computational or otherwise). The present work focusses on this assumption, tracing complications associated with presupposition and ambiguity to it. A family of modal logics is outlined, under which non-monotonicity can be analyzed as the failure of a sentenceby- sentence translation of a sequence of natural language sentences to persist; that is, the SR associated with a sentence may, in light of further natural language input, need to be revised. This revision may involve adjustments to background assumptions, implicated in presupposition accommodation.